2018
DOI: 10.1590/s2175-97902017000317003
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and histopathologic biomarkers of exposure to bisphenol-A in the freshwater fish, Ctenopharyngodon idella

Abstract: Bisphenol-A (BPA) belongs to the family of endocrine disrupting chemicals (EDCs) and it is used in the production of polycarbonate plastic and epoxy resins. The reproductive toxicity of BPA is well documented but it also exerts its toxic effects through multiple pathways especially by inducing a state of oxidative stress and causing damage to the vital organs. In the present study, histopathologic and oxidative damage caused by BPA in liver and kidneys of fresh water cyprinid, Ctenopharyngodon idella was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 45 publications
(38 reference statements)
8
30
0
Order By: Relevance
“…Woo et al (2014) reported increase in GST activity in Oryzias javanicus after exposure to BPA in sea water. Activity of GST also increased in kidney and liver of grass carp after exposure to 3 mg/l of BPA (Faheem and Lone 2017). Increased activity of GST was also reported in pearl mullet hepatocytes after exposure to BPA (Kaya and Kaptaner 2016).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Woo et al (2014) reported increase in GST activity in Oryzias javanicus after exposure to BPA in sea water. Activity of GST also increased in kidney and liver of grass carp after exposure to 3 mg/l of BPA (Faheem and Lone 2017). Increased activity of GST was also reported in pearl mullet hepatocytes after exposure to BPA (Kaya and Kaptaner 2016).…”
Section: Discussionmentioning
confidence: 53%
“…Supernatant was collected and absorbance was recorded at 532 nm. Glutathione was quantified by using the method of Jollow et al (1974) as described by Faheem and Lone (2017). Briefly, PMS was incubated with equal volume of 4% sulphosalicylic acid and incubated at 4°C for 60 min.…”
Section: Analysis Of Oxidative Stress and Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period water was replaced daily and fresh toxicant was added for 96 h. Fish were monitored at regular intervals and mortality data was recorded. The median lethal concentration (LC50) of DEP for 96 hours was calculated using probit regression analysis (Faheem and Lone, 2017). The experiment was conducted following OECD standardized guidelines for semi-static bioassays.…”
Section: Determination Of Median Lethal Concentration (Lc50) Of Depmentioning
confidence: 99%
“…While, the other portion of homogenate was used for estimating the levels of tissue lipid peroxidation. Enzymatic and nonenzymatic oxidative stress assays (CAT, GST, GSH and LPO) were performed by following the protocol of Faheem and Lone (2017). The GPx assay was performed by following the protocol of Mohandas et al (1984).…”
Section: Determination Of Enzymatic and Non-enzymatic Oxidative Stresmentioning
confidence: 99%